Relation between organizational commitment and professional commitment: an exploratory study conducted with teachers - Figueira, Dora de Jesus Guerreiro (2018)
The existence of several kinds of commitments in the workplace is well known. However, there are few studies that relate these different commitments or those established by deterministic models. This study explored the relationship between organizational and professional commitment in public higher education professors according to the multidimensional perspective of Meyer and Allen (1991), based on a convenience sample of 219 teachers. The proposed models were estimated through structural equation modeling methodology. Model 1 specified a relationship of direct influence of Professional Commitment on Organizational Commitment and Model 2 established the opposite relationship of direct influence of organizational commitment on professional commitment. Both models presented a good fit to the data without statistically significant differences between them. Nevertheless, the explanatory power of Model 1 was superior to Model 2, due to the fact that it includes a larger number of determinant relationships that are statistically significant. Theoretical and practical implications were discussed and new directions for future research were identified.